Optimizing mature oocyte yield in IVF: clinical comparison of r-hFSH+r-hLH and HMG in women with a stimulation dosage of at least 300 IU of gonadotropins - Fatemi, Human; Steinmacher, Sahra; Melado, Laura; ElKhatib, Ibrahim; Marqueta, Laura; Ruiz, Francisco; Del Gallego, Raquel; Kalafat, Erkan; Lawrenz, Barbara (Frontiers in Endocrinology, 2026)
ObjectiveTo study the impact of luteinizing hormone (LH) in stimulation medication on the mature oocyte yield obtained in in women receiving ovarian stimulation (OS) with a dosage of at least 300 IU gonadotropins.DesignRetrospective cohort study (01/2016-05/2024).SettingTertiary assisted reproductive technology center.PatientsWomen undergoing OS stimulation of at least 300 IU gonadotropins.InterventionOS using r-hFSH+r-hLH or HMG as stimulation medication.Main outcome measureRetrieved mature oocyte number.ResultsA total of 1,286 patients (696 in the HMG group and 590 in the r-hFSH+r-hLH group) were included in the unmatched cohort. Before matching, the r-hFSH+r-hLH versus HMG-groups showed significant differences in AMH (0.8 vs 1.2ng/mL,p<0.001), starting doses (85.1% vs 70.1% on 450IU,p<0.001), and categorized BMI distribution (p=0.003). After propensity score matching (age, BMI, AMH, basal FSH, starting dose), 1052 cycles were analyzed with a 1:1 match ratio. In the matched cohort after further adjusting for confounders, r-hFSH+r-hLH use was associated with significantly higher collected oocyte count (IRR 1.10, 95% CI 1.03-1.17, p=0.004) and mature oocyte count (IRR 1.12, 95% CI 1.04-1.21, p=0.003) compared to HMG. The sensitivity analysis looking at the interaction of AMH with gonadotropin type showed the effect is mostly significant for those with normal ovarian reserve (AMH between 1.0-3.5ng/mL, IRR: 1.19, 95% CI: 1.07 to 1.33, P = 0.001) but not for those with low (≤1ng/mL, P = 0.180) or high ovarian reserve (>3.5ng/mL, P = 0.932). Analysis of maturation rates showed no significant effect of medication type (p=0.143). The euploid blastocyst count after stimulation in the matched cohort and HMG use was associated with a 22% lower yield compared to r-hFSH+r-hLH (IRR 0.78, 95% CI 0.66-0.93, p=0.006) after adjusting for AMH, basal FSH, female age, dose, body mass index.ConclusionThe use of r-hFSH+r-hLH is associated with a significantly higher mature oocyte and euploid blastocyst count compared to HMG and the effect was most pronounced in women with normal ovarian reserve.